The Spillover Effects of the Global Crisison Economic Activity in Mena Emerging Market Countries : An Analysis Using the Financial Stress Index - Moriyama, Kenji (IMF Working Papers; Working Paper ;, 2010)
The estimated spillover of the global crisis to emerging market (EM) economies in the Middle East and North Africa (MENA) indicates that nearly two-thirds of the increased financial stress in MENA EM countries after the Lehman shock is attributable to direct or indirect spillovers of financial stress in advanced economies. Moreover, the estimated models suggest that the increased financial stress and slowdown in economic activity in advanced economies can explain about half of the drop in real GDP growth in MENA EM countries after the Lehman shock.